Ball possession as an indicator identifying differences in the efficient operation of football teams during the World Cup - Qatar 2022 - Soroka, A.; Duda, H.; Stula, A.; Ambrozy, T.; Kromke, C.; te Poel, H.-D. (Journal of Kinesiology and Exercise Sciences, 2023)
Background. Football game analysis is a key resource used in the training process. Such knowledge is achievable thanks to modern and advanced technologies whose task is to analyze traffic. The aim of the study was to determine and compare the values of game effectiveness indicators achieved by teams with a high percentage of possession of the ball (HPBPT)and teams with a lower percentage of ball possession (LPBPT). Materials and Methods. The study used analyzes of the performance of teams in 64 matches played during the football world cup - Qatar 2022. The study used platform for match analysis OPTA Sportsdata. The study used 31 performance indicators, which were divided into four groups. STATISTICA 13 PL (TIBCO Software, PaloAlto, CA, USA) software in it a discriminant function and the t - Student test were used to conduct statistical analysis. Results. Higher values of all analyzed parameters of shots, passes and offensive actions were obtained by HPBPT. Defensive action indicators such as: interceptions, clearances and block a shot mialy wyzsze wykonanie wsród LPBPT. The greatest impact on the effectiveness of the game had: creating goal action, shot reliability, shot pass reliability, medium pass reliability, possession of the ball, passes attempted from, free kicks and through passes. Conclusions. The study showed the importance of higher ball possession percentages for HPBPT teams. The study brings a new perspective on ball possession as a complex phenomenon that requires systematic monitoring. Teams with high sports mastery are able to put pressure on opponents by keeping possession of the ball longer during the game building phase.